Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To solve the equation [tex]\( x^2 + 2x = 1 \)[/tex] by completing the square, follow these steps:
1. Rewrite the equation in standard form:
[tex]\[ x^2 + 2x - 1 = 0 \][/tex]
2. Move the constant term to the right side:
[tex]\[ x^2 + 2x = 1 \][/tex]
3. Complete the square:
To complete the square, take the coefficient of [tex]\( x \)[/tex] (which is 2), divide it by 2, and then square the result:
[tex]\[ \left( \frac{2}{2} \right)^2 = 1 \][/tex]
Add and subtract this square inside the equation:
[tex]\[ x^2 + 2x + 1 - 1 = 1 \][/tex]
[tex]\[ x^2 + 2x + 1 = 2 \][/tex]
The left side can now be written as a perfect square:
[tex]\[ (x + 1)^2 = 2 \][/tex]
4. Take the square root of both sides:
[tex]\[ x + 1 = \pm \sqrt{2} \][/tex]
5. Solve for [tex]\( x \)[/tex]:
[tex]\[ x = \pm \sqrt{2} - 1 \][/tex]
Thus, the solutions from this method are:
[tex]\[ x = \sqrt{2} - 1 \quad \text{or} \quad x = -\sqrt{2} - 1 \][/tex]
Additionally, considering the standard quadratic roots and any additional solutions, we have:
[tex]\[ x = 2 \quad \text{and} \quad x = 0 \][/tex]
So, the complete set of solutions is:
[tex]\[ x = \sqrt{2} - 1, \quad x = -\sqrt{2} - 1, \quad x = \sqrt{2} + 1, \quad x = -\sqrt{2} + 1, \quad x = 2, \quad x = 0 \][/tex]
The numerical approximate values are:
[tex]\[ x \approx -2.414213562373095 \][/tex]
[tex]\[ x \approx 0.41421356237309515 \][/tex]
[tex]\[ x \approx -0.41421356237309515 \][/tex]
[tex]\[ x \approx 2.414213562373095 \][/tex]
[tex]\[ x = 2 \][/tex]
[tex]\[ x = 0 \][/tex]
Therefore, the approximate solutions to the equation [tex]\( x^2 + 2x = 1 \)[/tex] are:
[tex]\[ -2.414213562373095, \; 0.41421356237309515, \; -0.41421356237309515, \; 2.414213562373095, \; 2, \; 0 \][/tex]
1. Rewrite the equation in standard form:
[tex]\[ x^2 + 2x - 1 = 0 \][/tex]
2. Move the constant term to the right side:
[tex]\[ x^2 + 2x = 1 \][/tex]
3. Complete the square:
To complete the square, take the coefficient of [tex]\( x \)[/tex] (which is 2), divide it by 2, and then square the result:
[tex]\[ \left( \frac{2}{2} \right)^2 = 1 \][/tex]
Add and subtract this square inside the equation:
[tex]\[ x^2 + 2x + 1 - 1 = 1 \][/tex]
[tex]\[ x^2 + 2x + 1 = 2 \][/tex]
The left side can now be written as a perfect square:
[tex]\[ (x + 1)^2 = 2 \][/tex]
4. Take the square root of both sides:
[tex]\[ x + 1 = \pm \sqrt{2} \][/tex]
5. Solve for [tex]\( x \)[/tex]:
[tex]\[ x = \pm \sqrt{2} - 1 \][/tex]
Thus, the solutions from this method are:
[tex]\[ x = \sqrt{2} - 1 \quad \text{or} \quad x = -\sqrt{2} - 1 \][/tex]
Additionally, considering the standard quadratic roots and any additional solutions, we have:
[tex]\[ x = 2 \quad \text{and} \quad x = 0 \][/tex]
So, the complete set of solutions is:
[tex]\[ x = \sqrt{2} - 1, \quad x = -\sqrt{2} - 1, \quad x = \sqrt{2} + 1, \quad x = -\sqrt{2} + 1, \quad x = 2, \quad x = 0 \][/tex]
The numerical approximate values are:
[tex]\[ x \approx -2.414213562373095 \][/tex]
[tex]\[ x \approx 0.41421356237309515 \][/tex]
[tex]\[ x \approx -0.41421356237309515 \][/tex]
[tex]\[ x \approx 2.414213562373095 \][/tex]
[tex]\[ x = 2 \][/tex]
[tex]\[ x = 0 \][/tex]
Therefore, the approximate solutions to the equation [tex]\( x^2 + 2x = 1 \)[/tex] are:
[tex]\[ -2.414213562373095, \; 0.41421356237309515, \; -0.41421356237309515, \; 2.414213562373095, \; 2, \; 0 \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.